Residence time calculations for complex swirling flow in a combustion chamber using large-eddy simulations. (15th December 2016) - Doost, A.S.; Ries, F.; Becker, L.G.; Bürkle, S.; Wagner, S.; Ebert, V.; Dreizler, A.; di Mare, F.; Sadiki, A.; Janicka, J.
Abstract: In order to appraise the residence time calculation for a fluid element within a complex combustion system, which features oxy-fuel combustion, large-eddy simulations (LES) are carried out under cold flow conditions in a complex swirled flow generic laboratory-scaled combustor. The quantities, like residence time distribution, mean residence time, cumulative distribution function, variance and skewness, are used to characterize the configuration under investigation. To accurately account for the influence of the flow and to capture the tracer concentration evolution, LES are first assessed by comparison with statistical moments from experiments and by various indices of quality and error analysis. They show that the investigated configuration features a non-ideal reactor based on the flow and tracer transport. The calculated residence time distribution is analyzed and compared with experimental findings providing an estimated mean residence time of about τ =1.9 s. The derived residence time and functions are afterwards used to make predictions of tracer concentration at the reactor outlet. It turns out that such an appraised LES methodology is able to capture the residence time distribution in an accurate manner which allows its further extension to reacting conditions. Abstract : Highlights: Complex swirled turbulent flow in combustion chamber. Flow and tracer transport characterization by experiments. Comparison/validation with large-eddy simulations (LES). LES quality and error assessment. Characterization and evaluation of the residence time distribution using LES.